2002
DOI: 10.1038/modpathol.3880564
|View full text |Cite
|
Sign up to set email alerts
|

The Utility and Cost Effectiveness of Voice Recognition Technology in Surgical Pathology

Abstract: Voice recognition (VR) technology in computer systems converts speech directly into electronic text. In pathology, VR holds promise to improve efficiency and to reduce transcription delays and costs. We investigated the utility and cost effectiveness of targeted VR deployment in surgical pathology. A VR system was deployed for entry of gross descriptions of biopsies and of low to moderate complexity specimens and for entry of final reports for specimens not requiring microscopic analysis. Templates for VR were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 4 publications
1
19
0
1
Order By: Relevance
“…Most successful implementations have been performed in radiology or emergency services. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The primary reason for this observation seems to be the fact that, within these 2 medical specialties, there are several highly repetitive phrases that can be well understood by the computer. This is not the case in pediatric subspecialty practices.…”
Section: Discussionmentioning
confidence: 99%
“…Most successful implementations have been performed in radiology or emergency services. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The primary reason for this observation seems to be the fact that, within these 2 medical specialties, there are several highly repetitive phrases that can be well understood by the computer. This is not the case in pediatric subspecialty practices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although helpful for medication management,18 barcode systems do not support free text to allow the entry of rich clinical data (change in task). In addition, speech recognition systems work well when vocabularies are limited and dictation tasks are performed in isolated, dedicated workspaces, such as radiology or pathology,19 but are much less suitable in noisy public spaces, where performance is poor and the confidentiality of patient health information is threatened (change in environment). Tablet personal computers are generally accepted by physicians; however, their weight and fragility reduce acceptability by nurses (change in user) 20…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] However, there have been only a few studies comparing the use of voice recognition software with transcription services for surgical pathology. A study from the Cleveland Clinic 8 (Cleveland, Ohio) in 2002 reported the potential financial benefits and its experience with the implementation of VRT into surgical pathology. In 2003, a group in Ontario 1 reported that VRT had a lower accuracy and required more editing time than use of their human transcription service.…”
mentioning
confidence: 99%